Measuring disadvantage: changes in the underprivileged area, Townsend, and Carstairs scores 1981-91. (December 1995) - Dolan, S A; Jarman, B; Bajekal, M; Davies, P M; Hart, D
Abstract : OBJECTIVE–To compare the intercensal change for each of the underprivileged area (UPA), Townsend, and Carstairs scores calculated from 1981 and 1991 census data. SETTING–England and Wales. METHODS–The method described enables comparison of change in composite scores such as the UPA, Townsend, and Carstairs scores which are derived from normalised variables. The national values of equivalent variables derived from the censuses are calculated and normalised on the same baseline of the 1981 electoral ward mean and SD values. The resultant change in composite scores for different censuses can then be compared directly. MAIN OUTCOME MEASURE–Change in the composite score values for the 1991 census when compared with the 1981 census. RESULTS–For England and Wales, the UPA score increased by 5.62 units (0.35 of the SD) but the Townsend and Carstairs scores fell by 2.39 and 1.13 units respectively (0.71 and 0.33 of the SDs). CONCLUSION–The Townsend and Carstairs scores are good measures of material deprivation and show a general improvement as such between 1981 and 1991. The UPA score, however, includes additional factors relating to family structure, social deprivation, and health need and shows a decline in the overall situation.